Link Group Parametric Modeling and Optimal Design in Multi-arm Mechanical Arm System - Qi Zhu; Hua Long; Zhihong Zhou; Qichuang Zhang (Jixie chuandong)
Aiming at the problems of low calculation efficiency and conservative optimization design method of link in multi-arm mechanical arm system， taking the concrete pump truck as a typical engineering equipment component， the cylinder and link between the arm units are considered as one link group， the ANSYS APDL language is applied for the parametric modeling， and the optimization analysis is carried out under multiple working conditions， the optimal structure model of the link group is obtained. The feasibility of the calculation method is verified by the structural stress test. The results show that， the calculation efficiency of links is greatly improved with the methods of parametric modeling and optimal design， a feasible and effective method is provided for the design of links in the multi-arm manipulator system， and an important reference is provided for the design of components with similar structures.